Virtual Experiments of DNA Isolation and Hybridoma Techniques to Improve Students' Critical Thinking Ability (Biosaintifika: Journal of Biology & Biology Education, 2023)
Virtual learning during the Covid-19 pandemic always requires innovation from educators to present effective and interesting learning. The case method is an alternative learning method that can be used to increase awareness responses to problems contextually. This study aims to determine the effectiveness of implementing the use of virtual DNA isolation experiments and hybridoma techniques on students' critical thinking skills. The research was conducted on students majoring in Integrated Science, Semarang State University in the 2021-2022 academic year. Samples from the population are divided into experimental class and control class. The research instrument used to measure critical thinking skills uses a test. The results of the assessment of critical thinking skills were analyzed using quantitative analysis. The results showed that the experimental class obtained an average critical thinking ability of 87.86 and the control class obtained an average critical thinking ability of 73.86. The results of the posttest difference test analysis between the experimental class and the control class obtained a sig. (2-tailed) 0.000 less than the t table significance value of 0.05. Based on these results it can be concluded that the implementation of the use of virtual DNA isolation experiments and hinridoma techniques is effective in increasing students' critical thinking skills. The novelty of the results is virtual experiments of DNA Isolation and Hibridoma can be an alternative to virtual practice for schools with incomplete laboratory facilities.